2023
DOI: 10.1038/s41418-023-01117-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma cells lacking pro-apoptotic BAX are highly resistant to BH3-mimetics targeting pro-survival MCL-1 but retain sensitivity to conventional DNA-damaging drugs

Abstract: BH3-mimetic drugs are an anti-cancer therapy that can induce apoptosis in malignant cells by directly binding and inhibiting pro-survival proteins of the BCL-2 family. The BH3-mimetic drug venetoclax, which targets BCL-2, has been approved for the treatment of chronic lymphocytic leukaemia and acute myeloid leukaemia by regulatory authorities worldwide. However, while most patients initially respond well, resistance and relapse while on this drug is an emerging and critical issue in the clinic. Though some stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The level of MDA (Figure 3E) showed fructose induce systemic oxidative stress which are similar with other previous study. Bcl-2 is an anti-apoptotic protein while Bax is a kind of pro-apoptotic protein 40 , Bax expression increased, and Bcl-2 decreased stated that the original balance of cell growth and death was broken in excessive fructose intake.…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…The level of MDA (Figure 3E) showed fructose induce systemic oxidative stress which are similar with other previous study. Bcl-2 is an anti-apoptotic protein while Bax is a kind of pro-apoptotic protein 40 , Bax expression increased, and Bcl-2 decreased stated that the original balance of cell growth and death was broken in excessive fructose intake.…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…While proliferation rates and sensitivity to chemotherapeutic drugs and other cell death inducing agents were unchanged, VEN-insensitivity of cells (in five biological replicates) was stable, irrespective of exposure to VEN. Previous studies have shown that adaptation of tumor cells to VEN is characterized by different mechanisms resulting in functional loss of pro-apoptotic regulators like BAD, BAX, NOXA and PUMA or by a shift in dependency from BCL-2 to other anti-apoptotic proteins like MCL-1 [ 26 , 41 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of BAX has been described in VEN-resistant CLL cell lines and patient samples without concurrent BAX mutations [ 48 ], as we have observed upon modeled VEN-resistance in ALL. Interestingly, BAX knockout in B-cell lymphoma cells did not result in decreased VEN-sensitivity [ 50 ], further indicating that BAX-deficiency (due to gene alteration or other mechanisms) on its own impairs VEN-sensitivity in some contexts but does not seem to be a general mechanism of VEN-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Primary and HRP-conjugated secondary antibodies are listed in Supplementary Tables 2 and 3 , respectively. Western blotting performed as described previously [ 41 ].…”
Section: Methodsmentioning
confidence: 99%